COVID-19 vaccine hesitancy and its predictors among healthcare workers in a tertiary hospital in Ghana: A cross-sectional survey - Israel Abebrese Sefah; Perry Ofori; Araba Hutton-Nyameaye; Peter Yamoah; Frank Baiden; Varsha Bangalee (PLoS ONE, 2025)
Background Vaccination is one of the most effective public health interventions, but its hesitancy still poses a challenge in achieving acceptable coverage. This study was designed to assess the level of COVID-19 vaccine hesitancy and identify its influencing factors among healthcare workers in a teaching hospital in Ghana. Method A self-administered questionnaire was used to collect data. Descriptive statistics, Chi-square test of independence, and multiple logistic regression were assessed from the data collected using Stata version 14 software. Results A response rate of 78.55% (n = 216/275) was recorded. The majority of the participants were females (n = 135, 62.50%), aged between 20–39 years (n = 204, 94.44%), and were nurses/ midwives (n = 140, 64.81%) followed by medical doctors (n = 43, 19.91%). COVID-19 vaccine hesitancy was 19.91% and the commonly cited reasons for this were apathy (n = 8/43, 18.60%) followed by the belief of not being at risk of infection with the virus (n = 7/43, 16.28%). Hesitancy was reduced by participant’s knowledge of the vaccine effectiveness (aOR= 0.01; CI 95%: 0.001–0.0996; p < 0.001), COVID-19 training (aOR= 0.34; CI 95%: 0.13–0.85; p = 0.022), having a past vaccination history (aOR= 0.18, CI 95%: 0.07–0.45; p < 0.001), and increased by those with the view that vaccine intake should be voluntary (aOR= 3.28; CI 95%: 1.08–10.01; p = 0.037). Conclusion COVID-19 vaccine hesitancy was recorded among healthcare workers in this teaching hospital with apathy and belief of no risk to being infected by the virus as commonly cited reasons for this. This is a concern as healthcare workers are expected to be well-informed of the benefits and risks of vaccination. Continuous education on vaccine safety and efficacy can improve vaccine uptake among this population.